R&D Work Climate and Innovation in Semiconductors - Abbey, Augustus; Dickson, John W. (Academy of Management Journal, 1983)
The article discusses a research on research-and-development (R&D) work climate and innovation in the semiconductor industry. The perceptions of respondents with regard to work climate were computed, and each of the work climate dimensions was ranked. Results indicated that performance reward dependency and flexibility are essentially related to the number of innovations for all stages of innovation. Findings showed that work climate of innovative R&D subsystems is characterized by a reward system that recognizes and rewards excellent performance, and by a willingness to take risks and experiment without creative ideas and proposals.